Health professionals' knowledge of prevention strategies and protocol following percutaneous injury - C Bodkin (AOSIS, 2003)
Prevention strategies and protocols for the management of percutaneous injuries are developed for the purpose of preventing transmission of HIV and other infections. However, implementation thereof requires health professionals to be conversant with the content of protocols and ways to prevent percutaneous injuries. The purpose of the study was to determine health professionals' knowledge of prevention strategies and protocols following percutaneous injury. The purpose was addressed within a quantitative survey design. Data were collected by means of a self-administered questionnaire. The study was conducted at a public-sector tertiary academic hospital in Gauteng. Seven units within the hospital were randomly selected for investigation. These included, trauma, intensive care, medical, surgical, maternity, theatre and paediatrics. A population of 800 health professionals worked within the sampled units. Health professionals were stratified according to the following three categories, doctors, registered and enrolled nurses and medical and nursing students. A sample size of 200 health professionals was purposively selected of which a response rate of 79.5% (n= 159) was achieved. The sample consisted of 76.7 % (n=122) registered and enrolled nurses, 13.2% (n=21) doctors and 8.8% (n=14) medical and nursing students; 1.3% (n=2) did not specify their health professional category.